Child Custody after Divorce (Case Study of Court Decision Number 242/Pdt.G/2019/PN.Tjk) - Amalia Damayanti; Mohammad Fajri Mekka Putra (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
Marriage is the legally or formally recognized union of two people, a man and a woman, as partners who are physically and mentally bonded with the aim of forming a harmonious family or household. However, not all marriages last forever. When a marriage ends, divorce can occur. Divorce itself brings legal consequences, one of which is regarding child custody. Child custody after the occurrence of a divorce based on the provisions of Article 41 letter (a) of Law Number 1 of 1974 stipulates that both parents are obliged to continue to care for and educate their child for the benefit of the child and if there is a dispute regarding the control of the child, the court gives its decision. However, in reality a lot has happened in nurturing and educating child after the divorce, as in the case of Number 242/Pdt.G/2019/PN.Tjk.